Jesus in an age of terror : scholarly projects for a new American century - Crossley, James G. (London ; Oakville, CT : Equinox Pub., 2008)
This book applies the work of Noam Chomsky, Edward Herman, Edward Said and several others on international politics and the supportive role of the media, intellectuals and academics to contemporary Christian origins and New Testament scholarship. Part One looks at the ways in which New Testament and Christian origins scholarship has historically been influenced by its political and social settings over the past hundred years or so. Part Two looks at the Orientalist rhetoric of clashing civilisations and how this relates to the 'war on terror' and the creation of Islam, Arabs, Middle East etc.
Introduction : reading the history of New Testament and Christian origins scholarship -- The politics of the bibliobloggers -- The context : a clash of civilizations? -- Anglo-American power and liberal scholarship : scholarly reconstructions of the social world of Christian origins -- The context : Jesus and Christian origins since 1967 -- Jewish, but not that Jewish.
Includes bibliographical references (pages 238-255) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; Neues Testament; Christianity -- Origin; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Christianity -- Origin; Christentum; Entstehung; Rezeption; Theologie; Disziplin; Judaistik; Nahostkonflikt; Orientalistik; Bibelwissenschaft; Christentum; Rezeption; Aktualität.; Politik; Politischer Konflikt; USA; Christentum; Entstehung; Rezeption; Theologie; Disziplin (Wissenschaft); Judaistik; Nahostkonflikt; Orientalistik; Bibelwissenschaft; Geschichte 1900-2000; Geschichte 1967-2000; Electronic books; Criticism, interpretation, etc